Rapid screening and diagnosis of tuberculosis: a real challenge for the mycobacteriologist. - Zakham, F.; Akrim, M.; El mzibri, M.; Benjouad, A.; El aouad, R.; Ennaji, M. M. (Cellular and Molecular Biology, 2012)
Tuberculosis (TB) is an infectious, devastating and contagious disease, which infects third of the global population worldwide with high rates of incidence in the developing countries, where the health care providers face a serious problem and a real challenge during their clinical practice for controlling and preventing the transmission of this illness. Indeed the first step of control is the correct diagnosis and the initiation of the drug treatment regimen at the early stage of infection, which mandate the rapidity of screening and the accuracy of laboratory testing. In this paper we aim to highlight the different actual techniques, regarding the rapid screening and diagnosis of tuberculosis.